On the symbolism of 14th-century genre scenes depicted in the architectural sculpture of two impost friezes of the collegiate church in Sandomierz - Tuszyńska-Szczepaniak, Olga (Ars inspiratio: Studies dedicated to Professor Eleonora Jedlińska, 2024)
Gothic collegiate church of the Nativity of the Blessed Virgin Mary in Sandomierz, founded by king Casimir the Great, has an interesting set of architectural sculptures within the keystones, corbels and impost friezes. Most of them are examples of high-class art. Among the rich floral decorations in the capital zone of the temple, there are images of animals and fantastic creatures. Particularly noteworthy are the sculptural decorations on the friezes of two pairs of pillars, located on the line of the two entrances to the temple – the northern and southern one. They depict dogs chasing a hare and a dog chasing a hedgehog. These scenes are unique not only because of the visible interactions that carry the content of medieval symbolism, but also provide an opportunity to try to understand the ideological program of the architectural sculpture of the Sandomierz collegiate church. The key to understanding it are the texts of church fathers, physiologists and bestiaries along with rich medieval iconography.